2011
DOI: 10.1261/rna.029231.111
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide modifications and tRNA anticodon–mRNA codon interactions on the ribosome

Abstract: We have carried out molecular dynamics simulations of the tRNA anticodon and mRNA codon, inside the ribosome, to study the effect of the common tRNA modifications cmo 5 U34 and m 6 A37. In tRNA Val , these modifications allow all four nucleotides to be successfully read at the wobble position in a codon. Previous data suggest that entropic effects are mainly responsible for the extended reading capabilities, but detailed mechanisms have remained unknown. We have performed a wide range of simulations to elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 63 publications
1
42
0
1
Order By: Relevance
“…These findings showed that all of the transfer RNAs (tRNA) had C and G in the first nucleotides for anti-codon usage among all of the amino acids and, consequently, codon-anti-codon interaction in messenger RNA (mRNA) translation would be very strong. As a result, the average binding energy in codon-anti-codon interaction in hepatitis C is more than that with human cell interaction with HCV, and the mRNA and tRNA translation is stronger here than among similar human cell components (30). Based on the nucleotide structure of the codons, different used codons have special interactive affinity to anti-codons, and this thus leads to different powers of translation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings showed that all of the transfer RNAs (tRNA) had C and G in the first nucleotides for anti-codon usage among all of the amino acids and, consequently, codon-anti-codon interaction in messenger RNA (mRNA) translation would be very strong. As a result, the average binding energy in codon-anti-codon interaction in hepatitis C is more than that with human cell interaction with HCV, and the mRNA and tRNA translation is stronger here than among similar human cell components (30). Based on the nucleotide structure of the codons, different used codons have special interactive affinity to anti-codons, and this thus leads to different powers of translation.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 1, the m.7551A > G mutation is localized at a highly conserved nucleotide (A37), adjacent (3′) to the anticodon of mt–tRNA Asp (22,23). There were no modifications of i 6 A37 or t 6 A37 in the human mitochondrial tRNA Asp (27), although the nucleotides at position 37 (A or G) of tRNAs are often modified by methylthiolation (2829). The modifications at position 37 were shown to contribute to the high fidelity of codon recognition and to the structural formation and stabilization of functional tRNAs (3033).…”
Section: Introductionmentioning
confidence: 99%
“…[28,29,30,31] In the present manuscript we report MD simulations of select tRNAs using the CHARMM36 force field[32] that was recently extended to included modified nucleotides. The simulations are designed to investigate the influence of the nucleotide modifications on tRNA structure and dynamics as well as the impact of Mg 2+ .…”
Section: Introductionmentioning
confidence: 99%